2004
DOI: 10.1210/jc.2003-030330
|View full text |Cite
|
Sign up to set email alerts
|

Marked Suppression of Dihydrotestosterone in Men with Benign Prostatic Hyperplasia by Dutasteride, a Dual 5α-Reductase Inhibitor

Abstract: Dihydrotestosterone (DHT) is the primary metabolite of testosterone in the prostate and skin. Testosterone is converted to DHT by 5alpha-reductase, which exists in two isoenzyme forms (types 1 and 2). DHT is associated with development of benign prostatic hyperplasia (BPH), and reduction in its level with 5alpha-reductase inhibitors improves the symptoms associated with BPH and reduces the risk of acute urinary retention and prostate surgery. A selective inhibitor of the type 2 isoenzyme (finasteride) has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
264
1
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(288 citation statements)
references
References 29 publications
8
264
1
9
Order By: Relevance
“…Subphysiologic levels of DHT may occur with the medical treatment for lower urinary tract symptoms (LUTS) that engages clinical use of 5-alpha reductase inhibitors and lowers the circulating level of DHT by as much as 80% [112]. The 5-alpha reductase inhibitors finasteride and dutasteride are reportedly associated with a greater risk of ED, ejaculatory dysfunction, and decreased libido compared with placebo [113,114].…”
Section: Optional Laboratory Testingmentioning
confidence: 99%
“…Subphysiologic levels of DHT may occur with the medical treatment for lower urinary tract symptoms (LUTS) that engages clinical use of 5-alpha reductase inhibitors and lowers the circulating level of DHT by as much as 80% [112]. The 5-alpha reductase inhibitors finasteride and dutasteride are reportedly associated with a greater risk of ED, ejaculatory dysfunction, and decreased libido compared with placebo [113,114].…”
Section: Optional Laboratory Testingmentioning
confidence: 99%
“…By contrast, a variety of studies, using various designs and testosterone formulations, over periods ranging from several months to 15 years, in men with a wide range of ages, have not revealed an increased risk of prostate cancer [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154]. A meta-analysis found that testosterone treatment in older men compared to placebo was not associated with a significantly higher risk of detection of prostate cancer [131], although the frequency of prostate biopsies was much higher in the testosterone-treated group than in the placebo group [131].…”
Section: Lower Urinary Tract Symptoms and Prostate Diseasementioning
confidence: 97%
“…10,[33][34][35] As dutasteride inhibits both isoforms, it results in greater reductions in serum and intraprostatic DHT levels than finasteride. [36][37][38][39] REDUCE was a 4-year, multi-institutional, RCT of 0.5 mg daily oral dutasteride versus placebo in 8000 men. Inclusion criteria included PSA 2.5-10 ng ml -1 for men 50-60 years or 3.0-10 ng ml -1 for men 60-75 years; prostate volume o80 ml; American Urologic Association symptom score o25; and a prostate biopsy negative for cancer, high-grade prostatic intraepithelial neoplasia (HGPIN), and atypical small acinar proliferation within the earlier 6 months.…”
Section: Primary Preventionmentioning
confidence: 99%